2022
DOI: 10.1186/s12936-022-04187-6
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic paper analytical device using capture aptamers for the detection of PfLDH in blood matrices

Abstract: Background The prevalence and death rate arising from malaria infection, and emergence of other diseases showing similar symptoms to malaria require the development of malaria-specific and sensitive devices for its diagnosis. To address this, the design and fabrication of low-cost, rapid, paper-based analytical devices (µPAD) using surface-immobilized aptamers to detect the presence of a recombinant malarial biomarker—Plasmodium falciparum lactate dehydrogenase (rPfLDH)—is reported in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…544 Also, the enzymatic activity of Pf LDH captured on a lateral flow μPAD aptasensors was explored as means to detect this biomarker. 545 Ruiz-Vega et al reported a electrochemical POC paper device for quantitative detection of Pf LDH. The device featured a double-sided, screen-printed carbon electrode for detection of poly-HRP amplified magneto-immunoassays.…”
Section: Vector-borne Infectionsmentioning
confidence: 99%
“…544 Also, the enzymatic activity of Pf LDH captured on a lateral flow μPAD aptasensors was explored as means to detect this biomarker. 545 Ruiz-Vega et al reported a electrochemical POC paper device for quantitative detection of Pf LDH. The device featured a double-sided, screen-printed carbon electrode for detection of poly-HRP amplified magneto-immunoassays.…”
Section: Vector-borne Infectionsmentioning
confidence: 99%